The elements of investing - Malkiel, Burton Gordon (J. Wiley & Sons, 2010)
Lays to rest the popular shibboleths that undergird the hyperactive trading of the average investor. Addresses the essentials and offers a set of simple thoughts on how to enjoy the "winner's game" approach to investing.
Includes bibliographical references and index. - Print version record
Keywords: Investments; Finance, Personal; Portfolio management; Investment analysis; Investissements; Gestion de portefeuille; Analyse financière